The development of a web-based infographic for the introduction of palm industry to young learners - Shahrina Shahrani; Noor Faridatul Ainun Zainal; Rohizah Abd Rahman; Masura Rahmat; Azura Ishak; Mohammad Faidzul Nasrudin; Nik Aznizan Nik Ibrahim (Pejabat Karang Mengarang UPSI, 2023)
Exposure to the palm industry begins in the early stages of secondary school, highlighted through the agricultural sector topic in the geography subject syllabus. However, the information provided about the palm industry is insufficient to give young learners adequate exposure. Consequently, Generation Z lacks knowledge and remains unaware that the palm industry significantly contributes to the national economy. This paper aims to explain the process of developing an infographic website to expose the palm industry to young learners. The topics are traditionally presented using textbooks, but it is essential to incorporate information delivery methods in line with technological developments and interactive aspects to cater to today's Generation Z. An infographic website has been developed to introduce the palm industry to the younger generation, serving as a platform for information delivery and exposure. The website development process follows the Agile model, encompassing planning, analysis, design and development, testing, and deployment phases. Based on end-user testing involving 81 high school students who completed questionnaires, the three usability test criteria yielded an average score of 4.82 for web usability, 4.72 for information quality, and 4.82 for interface quality. The results of the students' feedback were positive, indicating that the infographic offered more detailed information, and the use of animation and posters provided a clearer depiction of palm industry-related information. In conclusion, an infographic website introducing the palm industry to the younger generation proves to be a suitable alternative for their initial exposure, garnering positive responses from this target group.